Penggunan web gis oleh pihak berkuasa perancangan : tinjauan kandungan dan tahap perkhidmatan yang disediakan - Haron, Haiza Wahida (2006)
An efficient planning process utilizes both information technology system and GIS. Both information technology system and GIS provide high capabilities in support decision making process, and provide accurate output that resemblance the real world situation. Web GIS is an advanced GIS and information technologies that capable to distribute spatial data in an open environment. Though, the wide used of this technologies among planning authorities didn’t reflect the exact used of web GIS for planning purpose. The main question emerge from this issue is, what are the exact web GIS content and services that suitable for planning authorities to serve the public interest, as well as planning agencies. Based on the issue, a study is made on the web GIS contents and level of services. Samples of web GIS from Malaysia and USA are teken into consideration. Observation study are done to analyze the content of web GIS. The Level Of Services (LOS) are analyze base on the Level Of Contents (LOC) and Level Of GIS Functions (LOF). Cross Tabular Matrix (CTM) approach are used to determine the level of services. LOS are rank from level A1 (lowest level) to level D4 (highest level). At level A1, the web GIS services are focus on delivering general information to the public. Level D4 represent the highest level of web GIS services, which is distributing information that supports decision making in planning process. Trough out the analysis, two web GIS; AGISwlk and OLIVER, were identified as web GIS under level D4. At the end, this study will come out with suggestions of guidelines to develop a web GIS suitable for planning authorities. The suggestions are made based on web GIS functions requirements, services and applications needed, identification of focus group and the user requirements, interface GIS functions and menus, and suitability of web GIS software